Ruddlesden–Popper‐Phase Hybrid Halide Perovskite/Small‐Molecule Organic Blend Memory Transistors. Issue 7 (31st December 2020) - Gedda, Murali; Yengel, Emre; Faber, Hendrik; Paulus, Fabian; Kreß, Joshua A.; Tang, Ming‐Chun; Zhang, Siyuan; Hacker, Christina A.; Kumar, Prashant; Naphade, Dipti R.; Vaynzof, Yana; Volonakis, George; et al.
Abstract: Controlling the morphology of metal halide perovskite layers during processing is critical for the manufacturing of optoelectronics. Here, a strategy to control the microstructure of solution‐processed layered Ruddlesden–Popper‐phase perovskite films based on phenethylammonium lead bromide ((PEA)2 PbBr4 ) is reported. The method relies on the addition of the organic semiconductor 2, 7‐dioctyl[1]benzothieno[3, 2‐b]benzothiophene (C8 ‐BTBT) into the perovskite formulation, where it facilitates the formation of large, near‐single‐crystalline‐quality platelet‐like (PEA)2 PbBr4 domains overlaid by a ≈5‐nm‐thin C8 ‐BTBT layer. Transistors with (PEA)2 PbBr4 /C8 ‐BTBT channels exhibit an unexpectedly large hysteresis window between forward and return bias sweeps. Material and device analysis combined with theoretical calculations suggest that the C8 ‐BTBT‐rich phase acts as the hole‐transporting channel, while the quantum wells in (PEA)2 PbBr4 act as the charge storage element where carriers from the channel are injected, stored, or extracted via tunneling. When tested as a non‐volatile memory, the devices exhibit a record memory window (>180 V), a high erase/write channel current ratio (10 4 ), good data retention, and high endurance (>10 4 cycles). The results here highlight a new memory device concept for application in large‐area electronics, while the growth technique can potentially be exploited for the development of other optoelectronic devices including solar cells, photodetectors, and light‐emitting diodes. Abstract : Blending the organic semiconductor 2, 7‐dioctyl[1]benzothieno[3, 2‐b]benzothiophene (C8 ‐BTBT) with the layered Ruddlesden–Popper‐phase perovskite (PEA)2 PbBr4 in solution phase facilitates the formation of large and near‐single‐crystalline‐quality platelet‐like perovskite domains overlaid by a thin layer of the organic molecule. Transistors utilizing the (PEA)2 PbBr4 /C8 ‐BTBT bilayer as the channel exhibit unexpectedly large hysteresis, and their use as a non‐volatile memory element is demonstrated.